Lung pharmacokinetics of inhaled and systemic drugs: A clinical evaluation. (11th August 2021) - Sadiq, Muhammad Waqas; Holz, Olaf; Ellinghusen, Birthe D.; Faulenbach, Cornelia; Müller, Meike; Badorrek, Philipp; Eriksson, Ulf G.; Fridén, Markus; Stomilovic, Stina; Lundqvist, Anders J.; Hohlfeld, Jens M.
Abstract : Background and Purpose: Human pharmacokinetic studies of lung‐targeted drugs are typically limited to measurements of systemic plasma concentrations, which provide no direct information on lung target‐site concentrations. We aimed to evaluate lung pharmacokinetics of commonly prescribed drugs by sampling different lung compartments after inhalation and oral administration. Experimental Approach: Healthy volunteers received single, sequential doses of either inhaled salbutamol, salmeterol and fluticasone propionate ( n  = 12), or oral salbutamol and propranolol ( n  = 6). Each participant underwent bronchoscopies and gave breath samples for analysis of particles in exhaled air at two points after drug administration (1 and 6, 2 and 9, 3 and 12, or 4 and 18 h). Lung samples were taken via bronchosorption, bronchial brush, mucosal biopsy and bronchoalveolar lavage during each bronchoscopy. Blood samples were taken during the 24 h after administration. Pharmacokinetic profiles were generated by combining data from multiple individuals, covering all sample timings. Key Results: Pharmacokinetic profiles were obtained for each drug in lung epithelial lining fluid, lung tissue and plasma. Inhalation of salbutamol resulted in approximately 100‐fold higher concentrations in lung than in plasma. Salmeterol and fluticasone concentration ratios in lung versus plasma were higher still. Bronchosorption‐ and bronchoalveolar‐lavage‐generated profiles of inhaled drugs in epithelial lining fluid were comparable. For orally administered drugs, epithelial‐lining‐fluid concentrations were overestimated in bronchoalveolar‐lavage‐generated profiles. Conclusion and Implications: Combining pharmacokinetic data derived from several individuals and techniques sampling different lung compartments enabled generation of pharmacokinetic profiles for evaluation of lung targeting after inhaled and oral drug delivery.